Meditative Movement Affects Working Memory Related to Neural Activity in Adolescents: A Randomized Controlled Trial - Kang, Hojung; An, Seung Chan; Kim, Nah Ok; Sung, Minkyu; Kang, Yunjung; Lee, Ul Soon; Yang, Hyun-Jeong (Frontiers in Psychology, 2020)
Numerous studies have revealed that meditative movement changes brain activity and improves the cognitive function of adults. However, there is still insufficient data on whether meditative movement contributes to the cognitive function of adolescents whose brain is still under development. Therefore, this study aimed to uncover the effects of meditative movement on the cognitive performance and its relation with brain activity in adolescents. Forty healthy adolescent participants (mean age of 17~18) were randomly allocated into two groups: meditative movement and control group. The meditative movement group was instructed to perform the meditative movement, twice a day for 9 minutes each, for a duration of 3 weeks. During the same time of the day, the control group was instructed to rest under the same condition. To measure changes in cognitive abilities, a dual n-back task was performed before and after the intervention and analyzed by repeated two-way analysis of variance (ANOVA). During the task, electroencephalogram signals were collected to find the relation of brain activity with working memory performance and was analyzed by regression analysis. A repeated 2-way ANOVA with Bonferroni correction showed that working memory performance was significantly increased by meditative movement compared with the retest effect. Based on regression analysis, the amplitude of high-beta rhythm in the F3 channel showed a significant correlation with dual n-back score in the experimental group after the intervention, while there was no correlation in the control group. Our results suggest that meditative movement improves the performance of working memory, which is related to brain activity in adolescents.